Retrograde evoked compound action potentials as an alternative for close-loop spinal cord stimulation - Nianshuang Wu; Zhen Wu; Cheng Zhang; Changzhe Wu; Xiaolin Huo; Jinzhu Bai; Guanghao Zhang (Scientific Reports)
Abstract Evoked compound action potential (ECAP) is an important parameter in close-loop spinal cord stimulation (SCS). The recording electrode is typically positioned proximal to the stimulation electrode to capture the antegrade ECAP signals generated by ascending fibers. However, relatively little research has been conducted on retrograde ECAPs. This study investigated retrograde ECAPs using custom-made epidural electrodes in 11 adult male Sprague–Dawley rats. Results show that the average motor threshold (MT) and ECAP threshold (ECAPT) for 11 anesthetized rats were 218.18 ± 69.54 μA and 107.27 ± 27.96 μA, respectively. The ECAP amplitudes increased with increasement of the stimulation current and pulse width (PW), and were larger in awake rats than in anesthetized rats. Additionally, aside from ECAPs recorded by a commercial electrophysiological recorder, ECAPs were also recorded by a custom-made amplifier for the purpose of future long-term implantation, but the custom-made amplifier showed lower signal to noise ratio than the commercial amplifier. In conclusion, this study illustrates that retrograde ECAP may also be considered as a feedback signal for close-loop SCS and more sophisticated ECAP recording circuits are needed to form a close-loop system.